Effect in vitro of the Phenobarbital on the Activity of the Enzyme Adenosine Triphosphatase (ATPase) of Sodium and Potassium Dependent in Human Placenta. - María De Jesús Sánchez Bouza; Pedro Sánchez Frenes (Centro Provincial de Información de Ciencias Médicas. Cienfuegos, 2007)
Background: Most of the drugs can pass to the fetus through the placenta, conditioning alterations of the development and fetal growth. Objective: To evaluate the effect in vitro of Phenobarbital on the activity of adenosine triphosphatase of sodium and potassium dependent in human placenta. Method: A study in vitro was carried out, in total homogenizes of placentas coming from 30 mothers that were assisted in the Gynecological and Obstetric Educational Provincial Hospital ¨Mariana Grajales¨, in Santa Clara, during the period March-July 1993. Phenobarbital was administered in concentrations of 0,1 mg/ml, 0,15 mg/ml and 0,2 mg/ml, keeping in mind the therapeutic dose to which was prescribed. The analyzed variables were: enzymatic activity and inhibition type. Results: The enzymatic activity of the adenosine triphosphatase of sodium and potassium dependent, diminished in a significant way, proportionally with the diminishment of the administered concentration of Phenobarbital. The inhibitory effect of the drug also turned out to be dependent of the concentration, presenting a major inhibition as the dose was increased. Conclusion: Phenobarbital produced highly significant decrease in the activity of adenosine triphosphatase of sodium and dependent potassium. This inhibition is of competitive type.